2021
DOI: 10.3390/jcm10184144
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Human Neutrophil Lipocalin Associates with Severe Acute Kidney Injury in SARS-CoV-2 Pneumonia

Abstract: Neutrophils have been suggested mediators of organ dysfunction in COVID-19. The current study investigated if systemic neutrophil activity, estimated by human neutrophil lipocalin (HNL) concentration in peripheral blood, is associated with acute kidney injury (AKI) development. A total of 103 adult patients admitted to intensive care, with PCR-confirmed SARS -CoV-2 infection, were prospectively included (Clinical Trials ID: NCT04316884). HNL was analyzed in plasma (P-HNL Dimer) and in whole blood (B-HNL). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, it is possible that the increased levels of histones are a marker of unspecific cell damage and are not linked to NET formation. Previous research shows that the number of neutrophils and markers of NETosis are elevated in severe COVID-19 patients [ 22 ], and a link has been suggested between NETosis and poor outcome [ 23 ], indicating a crucial contribution of NETs to the severity of the COVID-19 disease [ 24 , 25 ]. An association has also been described between anti-SARS-CoV-2 IgA2, NET formation and poor outcome [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible that the increased levels of histones are a marker of unspecific cell damage and are not linked to NET formation. Previous research shows that the number of neutrophils and markers of NETosis are elevated in severe COVID-19 patients [ 22 ], and a link has been suggested between NETosis and poor outcome [ 23 ], indicating a crucial contribution of NETs to the severity of the COVID-19 disease [ 24 , 25 ]. An association has also been described between anti-SARS-CoV-2 IgA2, NET formation and poor outcome [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that a delayed or absent adaptive immune response in critically ill patients with COVID-19 would cause higher mortality and organ failure. Several groups have also reported that SARS-CoV-2 can induce neutrophil extracellular trap (NET) formation in neutrophiles and that NET-formation could be part of the immunopathology in severe COVID-19 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One hundred and thirty two patients were admitted to the ICU (Intensive Care Unit) of Uppsala University Hospital with SARS-CoV-2 infections as diagnosed with PCR and signs of organ failure. Detailed information of the patient demographics was given previously [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…One hundred and thirty-two patients were admitted to the ICU (intensive care unit) of Uppsala University Hospital with SARS-CoV-2 infections as diagnosed with PCR and signs of organ failure. Detailed information of the patient demographics was given previously [10,11]. The healthy group consisted of 40 women (median age 32 years, range 22-64 years) and 18 men (median age 26 years, range 22-63 years).…”
Section: Methodsmentioning
confidence: 99%